2017
DOI: 10.1183/16000617.0116-2016
|View full text |Cite
|
Sign up to set email alerts
|

Acute respiratory distress syndrome

Abstract: Since its first description, the acute respiratory distress syndrome (ARDS) has been acknowledged to be a major clinical problem in respiratory medicine. From July 2015 to July 2016 almost 300 indexed articles were published on ARDS. This review summarises only eight of them as an arbitrary overview of clinical relevance: definition and epidemiology, risk factors, prevention and treatment. A strict application of definition criteria is crucial, but the diverse resource-setting scenarios foster geographic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
123
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(130 citation statements)
references
References 52 publications
0
123
1
2
Order By: Relevance
“…The glycocalyx is a negatively charged network that is composed of core proteins and side chains that modulate the microvascular environment, coagulation, thrombosis and vascular permeability (23). Edema and increased vascular permeability are the major characteristics of ARDS, which is a common manifestation of sepsis-associated organ dysfunction (24,25). The results of the present study demonstrated that UFH and NAH significantly alleviated lung edema and decreased the shedding of HS and SDC-1.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The glycocalyx is a negatively charged network that is composed of core proteins and side chains that modulate the microvascular environment, coagulation, thrombosis and vascular permeability (23). Edema and increased vascular permeability are the major characteristics of ARDS, which is a common manifestation of sepsis-associated organ dysfunction (24,25). The results of the present study demonstrated that UFH and NAH significantly alleviated lung edema and decreased the shedding of HS and SDC-1.…”
Section: Discussionmentioning
confidence: 55%
“…The associations between inflammation parameters, glycocalyx degradation products, and coagulation parameters were determined using a Spearman rank correlation test. Statistical analyses was conducted using SPSS v. 25.0 (IBM Corp). P<0.05 was considered to indicate a statistically significant difference.…”
Section: Measurement Of Lung Wet/dry (W/d) Weight Ratiomentioning
confidence: 99%
“…Since its first description, ALI/ARDS has been acknowledged to be a major clinical problem in respiratory medicine . The biology of CFs is complex and incompletely understood .…”
Section: Discussionmentioning
confidence: 99%
“…The acute respiratory distress syndrome (ARDS) refers to the critical medical condition characterized by serious inflammatory reaction in the lung, which may be caused by a range of diseases such as trauma, pneumonia and sepsis [1]. The clinical manifestations of ARDS include diffuse injury to the alveolar barrier cells, surfactant dysfunction, active innate immune response and unusual coagulation, which consequently and convergently result in the impairment of gas exchange function in the alveoli [2].…”
Section: Introductionmentioning
confidence: 99%